Eudragit® FS Microparticles Containing Bacteriophages, Prepared by Spray-Drying for Oral Administration - Emilie Tabare; Tiffany Dauchot; Christel Cochez; Tea Glonti; Céline Antoine; Fanny Laforêt; Jean-Paul Pirnay; Véronique Delcenserie; Damien Thiry; Jonathan Goole (MDPI AG, 2023)
Phage therapy is recognized to be a promising alternative to fight antibiotic-resistant infections. In the quest for oral dosage forms containing bacteriophages, the utilization of colonic-release Eudragit® derivatives has shown potential in shielding bacteriophages from the challenges encountered within the gastrointestinal tract, such as fluctuating pH levels and the presence of digestive enzymes. Consequently, this study aimed to develop targeted oral delivery systems for bacteriophages, specifically focusing on colon delivery and employing Eudragit® FS30D as the excipient. The bacteriophage model used was LUZ19. An optimized formulation was established to not only preserve the activity of LUZ19 during the manufacturing process but also ensure its protection from highly acidic conditions. Flowability assessments were conducted for both capsule filling and tableting processes. Furthermore, the viability of the bacteriophages remained unaffected by the tableting process. Additionally, the release of LUZ19 from the developed system was evaluated using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) model. Finally, stability studies demonstrated that the powder remained stable for at least 6 months when stored at +5 °C.